The Influence of Price, Product Quality, and Brand Image on Purchase Decisions of Lifebuoy Bath Soap - Jeselyn Jeselyn; Susanti Susanti; Angel Angel; Litka Tiadoraria br. Ginting (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The objective of this study is to evaluate how price, product quality, and brand image influence consumers' purchase decisions of Lifebuoy bath soap on the Shopee platform, specifically among Management students at Mikroskil University in 2022. This research is grounded in the growing interest in online shopping among younger generations and the importance of understanding the factors that affect consumer decision-making when selecting personal care products on e-commerce sites.This study employed a descriptive quantitative method with a survey approach, distributing questionnaires to 70 respondents selected using a saturated sampling technique. The collected data were analyzed using multiple linear regression with SPSS version 25.The results indicate that individually, price, product quality, and brand image each have a positive and significant effect on purchase decisions. Furthermore, these three factors collectively contribute to the purchase decisions of Lifebuoy bath soap. These findings suggest that companies need to pay close attention to setting competitive prices, continuously maintaining and improving product quality, and strengthening brand image to capture consumer attention on digital platforms. This study is expected to offer theoretical contributions in the field of marketing and provide practical insights for companies in designing more effective e-commerce-based marketing strategies.